On comparison of tuning method of FOPID controller for controlling field controlled DC servo motor. Issue 1 (1st January 2017) - Kumar, Prashant; Chatterjee, Shantanu; Shah, Devnath; Saha, U. K.; Chatterjee, Saibal
Abstract : In this paper, the Simulated Annealing (SA) optimization method is introduced to estimate the parameters of Fractional Order Proportional-Integral-Differential (FOPID) controller for controlling a field-controlled DC servo motor. The parameters are evaluated for considering a transfer function of controlling a field-controlled DC servo motor and its performance is observed for unit step response. Also, the parameters of FOPID controller are calculated using the traditional techniques such as Genetic Algorithm (GA) and frequency domain design method based on constrained optimization for the sake of comparison of performance with respect to simulated annealing method. A detail study on all the specified techniques is discussed in this paper.